Cosmogenic nuclide surface exposure dating of boulders on last-glacial and late-glacial moraines, Lago Buenos Aires, Argentina: Interpretive strategies and paleoclimate implications - Douglass, D. C.; Singer, B. S.; Kaplan, M. R.; Mickelson, D. M.; Caffee, M. W. (Purdue University, 2006)
in situ cosmogenic nuclides have become a powerful means to determine surface exposure ages of boulders on moraines and other landforms that are important to paleoclimate reconstructions. Potentially the largest and least quantifiable source of uncertainty of these surface exposure ages is the variable exposure histories of individual boulders. We use the mean square of weighted deviates (MSWD) statistic and cumulative frequency plots to identify groups of boulders that have statistically similar ages based on the number of analyses and their uncertainties. These samples most likely represent the true age of the moraine. We use these tools to interpret 49 Be-10 and Al-26 surface exposure ages of erratic boulders on six last-glacial and late-glacial moraines at Lago Buenos Aires, Argentina (LBA; 71 degrees W, 46.5 degrees S). Seven of the 49 boulders are identified as anomalously young, and are interpreted to have been exhumed after moraine deposition. The remaining 42 samples indicate that glacial advances or still-stands of the ice margin occurred at 22.7 +/- 0.9, 21.4 +/- 1.9, 19.9 +/- 1.1, 17.0 +/- 0.8, 15.8 +/- 0.6, and 14.4 +/- 0.9ka (weighted mean ages 2(+/- 2 sigma, analytical, erosion rate, and attenuation length uncertainties). This chronology of an outlet of the Patagonian Ice Cap is comparable to many records in the Northern Hemisphere despite a maximum in local summer insolation during this period. The implication is that climate during the Last Glacial Maximum was generally synchronous at the global scale. However, the late-glacial readvance to 95% of the extent of the largest advance during the Last Glacial Maximum at 14.4 +/- 0.9 ka is distinctively "Antarctic" in nature. It is contemporaneous with the Antarctic Cold Reversal, and precedes the Younger Dryas Chronozone. Further, our precise exposure ages highlight climatic asynchrony across southern South America between 23 and 14 ka. The timing of maximum ice extent and onset of deglaciation at LBA occurred similar to 4 ka later than in the ...